Sistema reprodutivo, distilia e graus de reciprocidade em rubiaceae arbustivas do sub-bosque de formações florestais do cerrado - Coelho, Christiano Peres (2013)
The heterostyly is genetically a flower polymorphism controlled where populations of plants present two or three morphs, that in natural areas in balance, it hopes to meet a same reason among the morphs (isoplethy). Those morphs are shown inside with reproductive pieces in different heights of the flower, in other words, with a space separation among anther/stigma, denominated herkogamy. In most of the species distylous, the herkogamy is usually shown in a reciprocal way. As larger the herkogamy smaller intrafloral the direct interference among the pieces sexual, and smaller the deposition of self pollen in the stigma, reducing the conflict among the sexual organs, in hermaphrodite flowers. The heterostyly is one of the characteristics more studied in flowering plant, that due to great variation that it can observe in several populations, mainly in the family Rubiaceae, that presents larger number of distylous species, compared with all the other botanical families. Those variations in forms distylous, forming populations monomorphic and/or homostylous, it can have a direct relationship with the habitat loss and the different selection pressures imposed in isolated forest fragments. The objective of the study was to evaluate the diversity of Psychotria and Palicourea in 20 forest fragments in the south area of the state of Goiás, characterizing the reproductive system, the characteristics heterostylous, the phenology and the pollination in five shrub species. Beyond of those objectives, evaluations of the degrees of reciprocal herkogamy intra and interspecific and also evaluations of herkogamy intrafloral in several species were tabulated. Trips were accomplished in 20 fragments in the south area of the state of Goiás, where it was evaluated the diversity of Psychotria and Palicourea and the reason among morphs of the species distylous in 10 of the 20 fragments, looking for relationship indications among the diversity of those goods with the environmental quality of the fragment. In one of those fragments, the reproductive system was evaluated, starting from manual pollinations, levels and incompatibility places starting from evaluation of growth of pollen tube, flower visitors and potential pollinators and phenology in five species of Rubiaceae, being them: Psychotria colorata, P. capitata, P. prunifolia, P. hoffamanseggianna and Palicourea croceoides. With the data morphometric of those species, and more the species Psychotria gracilenta, was calculated the levels of reciprocal herkogamy intra and interspecific, using for that, two different methods. The influence of the size of the corolla in the height of the sexual pieces and consequently in the reciprocity it was evaluated also of form intrafloral and interfloral. The levels of herkogamy intrafloral were also registered starting from a bibliographical rising in several works of Rubiaceae, finding 132 populations of 101 species of Rubiaceae distylous, monomorphic and homostylous, looking for indications of an evolutionary tendency for those variations. To the whole they were observed, in the appraised fragments, 64 populations of 10 different species, being eight species of Psychotria and two species of Palicourea. The most common species in the fragments was Psychotria prunifolia, found in 17 fragments, while P. hoffmannseggiana was identified in 15 fragments and P. capitata in 14 areas, some areas didn\'t present any species while another only presented one or two species. Any relationship was not evidenced among diversity of species with the size and environmental quality of the fragment. The reproductive data demonstrate that except Psychotria prunifolia all the other appraised species if they showed distylous, isoplethy and incompatible solemnity with inhibition of the pollen tubes in the stigma for the morph thrum and in the stigma and probe for the morph pin. The principal visitors and potentials pollinator were bees, moths and in the case of the species of Palicourea also hummingbirds. The reciprocity levels were not perfect for any appraised species, but they presented wide variation among the species. The populations of Palicourea croceoides, Psychotria colorata and Psychotria capitata evidenced high reciprocity values, while for the evaluation interspecific, the species Palicourea croceoides presented wide reciprocity with organs of Psychotria capitata, Psychotria colorata and Psychotria prunifolia, what can generate fecundity reduction due to contamination of the stigma for pollen interspecific. The size of the corolla influenced in a significant way in the height of the organs and consequently in the reciprocity levels, being the influence in the stamens adult\'s height than in the height of the pistils in all the appraised species. The evaluation of the herkogamy reciprocal interspecific, little appraised in the literature, it was justified due to the appraised species they be simpátricas, to superpose the flowering and they share the principal floral visitors (bees and moths of the day). Evaluation of the levels of reciprocal herkogamy among individuals of a population and enter species of an area it can be an important tool in the explanation of the atypical patterns of distilia found in species of the Savannah. The flowering of all the species is annual, and it happens between the months of November and March, with flowering pick in December and January, and flowering varying from three to five months. For the evaluation of the herkogamy intrafloral it was noticed that the individuals thrums presented a larger separation among stigma/anther, compared with the corolla in 74 (56%) of the 132 populations registered distylous, while the morph pin presented larger herkogamy in 58 (44%) of the populations sampled. The population monomorphic presented a reduction of 50% of the separation stigma/anther when compared with the population s distylous, and the populations homostylous they reduced in more than 90% that separation, compared with population s distylous. The data demonstrate an evolutionary tendency for the reduction of the separation stigma/anther (herkogamy) as the populations lose temper of typical distylous for monomorphic and homostylous. That behavior can be resulted of selection pressures and strategies of reproductive safety for the maintenance of the populations. Even with those tendencies being observed, those evolutionary roads, mainly in Rubiaceae they need many studies for they be elucidated, mainly in areas with report of pressures older anthropic and with species close phylogenetically.